The Reuse Process of OSS Components - Bae Kim, Jong; Jin Bae, Myung (International Journal of Engineering and Technology, 2018)
In recent years, OSS has been expanding globally, with the advantage of being able to avoid adverse consequences of proprietary software monopolies, and to reduce the budget and procedures for maintenance and upgrades.Â  This can serve as a good opportunity to prevent the monopoly of large corporations and establish a balanced industrial structure through fair competition. despite the many advantages of OSS, we are having difficulties in using OSS due to several reasons. To meet the functionality of the required software, leveraging open source is seen as an effective way to reduce costs and ensure quality. However, in the actual development process, it is difficult to select open source with proper function and quality, to analyze it, to change it, and to integrate it into the target system. In order to solve these problems, this study proposed the procedures and methods for identifying and selecting open source, and the efficient improvement and integration method through minimal modification.Â Â